Structural insights into the activity of enhancer-binding proteins. - Rappas, M; Schumacher, J; Beuron, F; Niwa, H; Bordes, P; Wigneshweraraj, S; Keetch, C; Robinson, C; Buck, M; Zhang, X (2005)
Activators of bacterial sigma54-RNA polymerase holoenzyme are mechanochemical proteins that use adenosine triphosphate (ATP) hydrolysis to activate transcription. We have determined by cryogenic electron microscopy (cryo-EM) a 20 angstrom resolution structure of an activator, phage shock protein F [PspF(1-275)], which is bound to an ATP transition state analog in complex with its basal factor, sigma54. By fitting the crystal structure of PspF(1-275) at 1.75 angstroms into the EM map, we identified two loops involved in binding sigma54. Comparing enhancer-binding structures in different nucleotide states and mutational analysis led us to propose nucleotide-dependent conformational changes that free the loops for association with sigma54.